Nine New Pregnane Glycosides from the Cultivated Medicinal Plant Marsdenia tenacissima - Qian-Qian Meng; Shun-Yao Tong; Xing-Rong Peng; Yu-Qing Zhao; Zheng-Hui Li; He-Ping Chen; Ji-Kai Liu (Molecules, 2023)
The ethnobotanical plant Marsdenia tenacissima has been used for hundreds of years for Dai people in Yunnan Province, China. Previously, chemical investigations on this plant have revealed that pregnane glycosides were the main biological constituents. Nine new pregnane glycosides, marsdeosides A–I (1–9), were isolated from cultivated dried stems of the medicinal plant Marsdenia tenacissima in this study. The structures were analyzed by extensive spectroscopic analysis, including 1D, 2D NMR, HRESIMS, and IR spectroscopic analysis. The absolute configurations of the sugar moieties were identified by comparing the Rf values and specific optical rotations with those of the commercially available standard samples and the data reported in the literature. Marsdeosides A (1) featured an unusual 8,14-seco-pregnane skeleton. Compounds 1, 8, and 9 showed activity against nitric oxide production in lipopolysaccharide-activated macrophage RAW264.7, with IC50 values of 37.5, 38.8, and 42.8 μM (L-NMMA was used as a positive control, IC50 39.3 μM), respectively. This study puts the knowledge of the chemical profile of the botanical plant M. tenacissima one step forward and, thereby, promotes the sustainable utilization of the resources of traditional folk medicinal plants.